Another brick in the wall: new record and key to Anastrepha Schiner, 1868 (Diptera, Tephritidae) from Pará, Brazil - Zucchi, Roberto A.; Araújo, Alexandre S.; Oliveira-Filho, Aprigio L. de; Pinto, Israel de S.; Aurélio, Mateus S. L.; Savaris, Marcoandre (Entomological Communications, 2025)
Despite advances in studies on fruit flies belonging to the genus Anastrepha Schiner, 1868 (Diptera: Tephritidae) in the state of Pará, Brazil, over the past two decades, knowledge of their diversity remains incipient, particularly when considering the vast geographical expanse of the state. Only 35% of the documented species have been associated with their respective hosts. Anyway, for Anastrepha parishi Stone, 1942, which is reported for the first time in Pará State, all records of this species in Brazil have been associated with their designated hosts. In addition to this new record, we discuss the distribution of Anastrepha consobrina (Loew, 1873) in Pará, whose original description was based on specimens collected in the state in the early 19th century. Since then, A. consobrina has not been collected in Pará. A key to the 40 species of Anastrepha known in Pará is presented.